The Role of KKN Students in the Era of Digitalization of Education in Gabanganom Wetan Village - Muhammad Syifa’ Nuqoba; Tasya Kurnia Yulia Putri; Alfiani Anditasari; Muhammad Zaki Adnan; Nova Riyanti; Eni Faujiyah Mailani; Syarifatul Aulia; Aghina Ragil Sugesta; Sulistio Sulistio (Universitas Palangka Raya, 2024)
In digitalization, education is a crucial element in developing individual potential and intelligence. To carry out education effectively in the era of digitalization, teaching staff are needed who can teach in formal and non-formal contexts, of course with their competencies. Our Real Work Lectures (KKN) are held in Gebanganom Wetan Village, Kangkung District, with the main aim of providing community service and supporting the improvement of children's education in the village. Even though the enthusiasm and passion for learning among children in Gebanganom Wetan Village is very high, the shortage of teaching staff is a major obstacle to achieving maximum education. This article is entitled